2012
DOI: 10.1515/jpm-2012-0020
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and developmental programming

Abstract: The environment in utero and in early neonatal life may induce a permanent response in the fetus and the newborn, leading to enhanced susceptibility to later diseases. This review concentrates on the role and mechanisms of events during the antenatal and immediate postnatal period resulting in later life diseases, concentrating on abnormal growth patterns of the fetus. Fetal overgrowth is related to exposure to a diabetic intra uterine environment, increasing the vulnerability to transgenerational obesity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 50 publications
1
38
0
1
Order By: Relevance
“…One of them could be the so-called fetal programming phenomenon, that is, the epigenetic alterations induced by the environment in which fetuses develop during pregnancy. This phenomenon is one of the key mechanisms leading to the development of metabolic disorders during adulthood in FGR infants 35,36 and could have many other consequences.…”
Section: Discussionmentioning
confidence: 99%
“…One of them could be the so-called fetal programming phenomenon, that is, the epigenetic alterations induced by the environment in which fetuses develop during pregnancy. This phenomenon is one of the key mechanisms leading to the development of metabolic disorders during adulthood in FGR infants 35,36 and could have many other consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of epidemiological (Barker et al 2002;Galjaard et al 2013;Gluckman et al 2007) and animal (Heindel 2008;McMullen and Mostyn 2009;Nathanielsz 2006) studies have shown that environmental challenges experienced by the developing mammalian organism in utero and in early neonatal life can induce a persistent response in a variety of organs, predisposing to enhanced susceptibility to later life onset of diseases such as type 2 diabetes (Portha et al 2011), hypertension (Ingelfinger and Nuyt 2012), obesity (Sarr et al 2012), and alterations in reproductive function (Zambrano et al 2014a). In the model studied here, we have previously reported that at PND 270, male offspring of mothers fed a low-protein diet during pregnancy had a lower sperm count and a 50 % decrease in fertility rate compared to controls (Zambrano et al 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exposure to an adverse intrauterine environment, namely an environment characterized by hyperglycemia and hyperinsulinemia, may influence epigenetics and the structural and functional adaptive responses responsible for developmental programming [15]. The increased risk of obesity is related to the degree of fetal hyperinsulinism [24].…”
Section: Diabetes and Intrauterine Programmingmentioning
confidence: 99%
“…GDM may thus result in both macrosomic offspring and intrauterine growth restriction [13] [24], depending on the degree of hyperglycemia presented [15] [21]. There is growing epidemiological evidence that excesso nutritional intake to the fetus can produce phenotypes similar to those of malnutrition in offspring [8].…”
Section: Diabetes and Intrauterine Programmingmentioning
confidence: 99%